ANALISIS NILAI TAMBAH DAN PRODUKSI INDUSTRI KERUPUK KEMPLANG DI KOTA PALEMBANG - Linda Linda; Taufiq Marwa; Suhel Suhel (Jurnal Ekonomi Pembangunan, 2004)
The tittle of this research is Value Added and Production Analysis of Kerupuk Kemplang Industry in Palembang. This research is aimed to know the value added thas has been resulted by the industry of kerupuk kemplang and how it is factor increased the produsction of kerupuk kemplang in Palembang. There are seme factors that influence the production of kerupuk kemplang, such as material, additional goods and labor. This research has been done in Seberang Ulu Palembang, which has taken twenty samples, which are considered to represent the kerupuk kemplang industries in Palembang. The sampling method, which has been taken, is purposive sampling. The sampling method that will not give the same possibility for all elements in populations to be chosen is perfectly stressed that is sample is taken by the criteria that is needed in this thesis. The value added from industries is output mim1s intermediate cost. This research is use production junction model from Cobb Douglas. The corelation of each variable could be seen of the regression below: Y = 0,9509338 + 0,838BB- 0,380BP + 0,492TK Based 0f the analysis of descriptive quantitative we get the value added of kerupuk kemplang industries in Palembang each year is Rp. 544.180.000 with the average of value added is Rp. 27.709.000. Basic commodity and labor have positive correlation to output with coefficient of elasticity 0,838 and 0,492 in 95% level of significant. Additional commodity has negative correlation to output with coefficient of elasticity -0,380. Additional commodity doesn't have strong corelation in 95% level of significant but in 84% level of significant it has. The industries of kerupuk kemplang in Palembang followed decreasing return to scale, where the total amount of a + P + y(0,838-   0,380 + 0,492) less than 1. From this thesis we could estimate that the producer  of kerupuk kemplang should note the quality, taste of kerupuk kemplang that has been produced as well. Beside that, the constant of movemment 'scrole in capitalize is needed as well. For the home industry of kerupuk kemplang: at also the workship. Between the producer of kerupuk kemplang and the producer of atenal .m order to support the productio11 it well without any difficulties in supplying the mam matenalKeywords: Value Added. Elasticity, Production